Intelligent monitoring and individualized strategies for preventing altitude sickness during altitude training - Li, L.; Fan, T.; Luo, Z.; Zhu, P.; Zhang, L. (Frontiers in Physiology, 2025)
Altitude training is a special training method that uses a hypoxic environment to improve athletic performance. Its scientificity and safety have always attracted much attention. The hypoxic environment at high altitudes causes physiological responses, such as decreased blood oxygen saturation, increased oxidative stress, and changes in vascular permeability. By establishing a multi-level physiological indicator monitoring system, including basic indicator monitoring, special function assessment, and new technology application, the training effect can be effectively evaluated, and the training safety can be guaranteed. In terms of training optimization, the application of individualized programs based on genetic testing and intelligent monitoring systems has significantly improved the scientificity of training. Among them, the step-by-step adaptation method combined with hypoxic pre-training reduce the incidence of acute mountain sickness by 75%, and the individualized program reduce the difference in training effects by 40%. However, altitude training still faces controversial issues such as the ethics of drug intervention and the effect of simulated training. Future research should focus on the gene-environment interaction mechanism, develop new monitoring technologies, and establish a multidisciplinary collaboration system. This review focuses on the physiological mechanisms, monitoring methods, optimization strategies, limitations and future development directions of altitude training in preventing altitude sickness. This provides an important basis for the scientific practice of altitude training. By continuously optimizing the training system, altitude training will become a safe and effective method to improve athletic performance and prevent altitude sickness.